2015 10th International Conference on Design &Amp; Technology of Integrated Systems in Nanoscale Era (DTIS) 2015
DOI: 10.1109/dtis.2015.7127378
|View full text |Cite
|
Sign up to set email alerts
|

Statistical lifetime analysis of memristive crossbar matrix

Abstract: Abstract-Memristors are considered one of the most favorable emerging device alternatives for future memory technologies. They are attracting great attention recently, due to their high scalability and compatibility with CMOS fabrication process. Alongside their benefits, they also face reliability concerns (e.g. manufacturing variability). In this sense our work analyzes key sources of uncertainties in the operation of the memristive memory and we present an analytic approach to predict the expected lifetime … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The r 1 to r N-1 are random numbers betw een 0 and 1. These random numbers are created as follow s: 1-Create m random numbers that sum up 1 2-Repeat step 1 α times, where α =N/m and make a set of random numbers (r 1 to r N ) 3-Use N-1 terms of the above set (r 1 to r N-1 ) for the calculation in (13) N ext, E(0) i s ev aluated mathematically from (18) and the above process (steps 1-3) i s repeated 10,000 times, each time with a different set of random portions (r 1 -r 2 ,….,r N-1 ). At the end all E(0) values are averaged from each iteration and the expected number of shifts in this scenario i s obtained.…”
Section: Finding the Number Of Shifts In Non-uniform Assumption Usingmentioning
confidence: 99%
See 2 more Smart Citations
“…The r 1 to r N-1 are random numbers betw een 0 and 1. These random numbers are created as follow s: 1-Create m random numbers that sum up 1 2-Repeat step 1 α times, where α =N/m and make a set of random numbers (r 1 to r N ) 3-Use N-1 terms of the above set (r 1 to r N-1 ) for the calculation in (13) N ext, E(0) i s ev aluated mathematically from (18) and the above process (steps 1-3) i s repeated 10,000 times, each time with a different set of random portions (r 1 -r 2 ,….,r N-1 ). At the end all E(0) values are averaged from each iteration and the expected number of shifts in this scenario i s obtained.…”
Section: Finding the Number Of Shifts In Non-uniform Assumption Usingmentioning
confidence: 99%
“…They will affect the normal operation of memory cell because for instance, process variability could cause variation in the nominal high and low re-si stance values, or endurance degradation will impose dynamic variation to the resi stance values due to aging mechanisms [12]. H aving these reliability considerations, it becomes necessary to analytically model and estimate the lifetime of memristive devices in presence of process variability and endurance degradation and then to design new and innovative architectures to overcome these draw back s [13]. At this point, one of the main interests for the researcher s is to design reconfigurable crossbarbased memory architectures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crossbar architectures are attractive due to the regularity and the integration density. They have become more popular for memristive devices for these reasons [5,19,36,37]. It has previously been shown that a general memcapacitive crossbar network can be built [45] and that such a crossbar network can perform a dot product [13].…”
Section: Memcapacitive Crossbar Classifiermentioning
confidence: 99%
“…Figure 3 shows the probability of failure when considering Reference=(LRS+HRS)÷2. The wide resistance distribution of RRAM cells can impose low read yields and can reduce the device lifetime [16], therefore it is needed to design variability tolerant circuits, presented in the next section.…”
Section: B Impact Of Rram Variabilitymentioning
confidence: 99%